Managing Banni grassland issues and opportunities - Dayal, Devi; Dev, Rahul; Sureshkumar, M.; Manjunatha, B. L. (Indian Farming, 2018)
The grasslands at Banni is in extreme degradation state and is being further degraded at faster rate. Uncontrolled grazing, increasing salinity and invasion of P. juliflora are the major factors causing accelerated degradation. Steps need to be taken for controlling the indiscriminate grazing and adequate control/ monitoring with local participation is necessary to give enough time for the pasture to develop. The system of deferred controlled grazing can be advocated. Adoption of scientific management practices with active involvement of stake holders and policy makers can only come to the rescue of the precious resources.